2011
DOI: 10.1002/hrdq.20078
|View full text |Cite
|
Sign up to set email alerts
|

Influences of formal learning, personal learning orientation, and supportive learning environment on informal learning

Abstract: While workplace learning includes formal and informal learning, the rela-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
187
1
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(203 citation statements)
references
References 51 publications
6
187
1
9
Order By: Relevance
“…Some studies have investigated how individual differences and the context affect informal learning. Choi & Jacobs (2011) found that personal learning orientation and participation in formal training positively influenced informal learning. Noe et al (2013) found that zest was the only significant predictor of informal learning when considered along with the Big Five traits and generalized self-efficacy.…”
Section: Informal Learningmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies have investigated how individual differences and the context affect informal learning. Choi & Jacobs (2011) found that personal learning orientation and participation in formal training positively influenced informal learning. Noe et al (2013) found that zest was the only significant predictor of informal learning when considered along with the Big Five traits and generalized self-efficacy.…”
Section: Informal Learningmentioning
confidence: 98%
“…Several studies have demonstrated the importance of a supportive learning culture in facilitating engagement in learning and knowledge-sharing behaviors. Choi & Jacobs (2011) found that a supportive learning environment had a significant positive indirect effect on informal learning through its influence on employees' participation in formal learning courses and programs. A supportive learning culture also has a positive and direct influence on team outcomes such as creativity and collaborative knowledge creation practices as well as an indirect effect on team performance (Yoon et al 2010).…”
Section: Work Environmentmentioning
confidence: 99%
“…Aprendizagens de competências se dão, contudo, de várias formas, cabendo às organizações oferecer suportes aos seus funcionários para que se engajem continuamente em processos de aprendizagem e também façam uso do aprendido, seja em situações de trabalho, seja em treinamentos formais (CHENG; HAMPSON, 2008;BLUME et al, 2010;CHIABURU;HUTCHINS, 2010;CHOI;JACOBS, 2011;NOE;CLARKE;KLEIN, 2014).…”
Section: Lívia Maria Reis Pereira Elisabeth Loiola and Sonia Maria Gueunclassified
“…The main role of adult training courses is to focus on the principles of stimulating, motivating, relevant and effective teaching with a concrete impact in professional and personal life, [2].…”
Section: Resultsmentioning
confidence: 99%